Fatwa as a Tool of Social Engineering: The Study of Fatwa of Tarjih Muhammadiyah - Mohammad Hasan Bisyri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
This article discusses the function of fatwa, specifically the Tarjih fatwa in the field of family law. So far, Islamic law is still considered not dynamic and limited to only one legal function, namely nahi munkar (social control), while the function of amar makruf (social engineering), which emphasizes encouraging good deeds in a general and practical sense, has not been optimized. This situation creates the impression that Islamic law is losing its relevance. This article aims to explain the function of Tarjih fatwa for the community. The study applies a literature review using a sociological approach. The results indicate that law (fatwa) is no longer viewed as an independent variable separated from other elements, but rather as a dependent variable, similar to social norms and other cultural identities. Tarjih fatwa is intended to direct society toward desired goals, eliminate inappropriate habits, and create new patterns of behavior. In other words, the function of Tarjih fatwa can be utilized as a means of influencing society (law as a tool of social engineering).